Deregulierung, Re-Regulierung: Auswirkungen der Rückvermeisterung im Handwerk - Petrik Runst; Jörg Thomä (Wirtschaftsdienst, 2024)
– The obligation to obtain a master craftsman's certificate in order to set up a new business was suspended in 2004 for some trades in the German skilled crafts sector, but was reintroduced for some of them in 2020. This paper presents the first empirical results of this re-regulation and places them in the context of the policy discussion. The results so far indicate a reversal of the 2004 deregulation effects on German crafts after the re-regulation. Future in-depth studies will show whether these effects are robust.
Keywords: L51; J44; J48; 330; Handwerk; Regulierung; Deutschland; Handwerk; Regulierung; Deutschland